Piramida: Peninggalan Karya Seni Dunia dari Wilayah Barat Hingga Timur (Bagian Ii) - Hanny Wijaya (Humaniora, 2011)
There is a terminology declared that human learn from the past to reach a better future. Based on this comprehension, human start to learn about history. Scientists learn history from historical building and cultural heritage from the past. One of the most important building that we need to learn is pyramid. For quite a long time, many people do not know the fact that actually pyramid was only a fundamental form. Everytime people hear a word ‘pyramid’, they will think directly and know globally about Egyptian Pyramid. Actually, there were so many different forms of pyramid scattered around the world, from western to eastern countries. Besides Egypt, some countries that have been well-known about their pyramids are Mesopotamia, Egypt, Sudan, Nigeria, Greece, Spain, China, Mexico, North America, Italy, India and Indonesia. In this continuous part of research, article discusses Chinese and Mexican or Mesoamerican Pyramids as the Eastern and American continent cultural heritage. Hopefully, this research will enhance the knowledge about pyramids more specific and reader will be able to differentiate the function and form of each pyramids in the world.